The Controllability and Observability of Sylvester Matrix Dynamical Systems on Time Scales (International Journal of Food and Nutritional Sciences, 2021)
In this paper, a solution for the first-order matrix dynamical system is derived, and a set of necessary and sufficient conditions for complete controllability and complete observability of the Sylvester matrix dynamical system is presented.